2012
DOI: 10.1016/j.jep.2012.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Omics and its potential impact on R&D and regulation of complex herbal products

Abstract: In traditional Chinese medicine (TCM), multicomponent and principally plant-derived drugs are used for disease prevention, symptom amelioration and treatment in a personalized manner. Because of their complex composition and consequent multiple targets and treatment objectives, the application of omics techniques and other integrative approaches seems inherently appropriate and even necessary for the demonstration of their potential preclinical and clinical safety and efficacy. This perspectives article provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 59 publications
0
36
0
Order By: Relevance
“…This confidence was reflected by the opinions of GP-TCM members in the "Grand Issues" survey and supported by the recent research developments reviewed in this special issue Jia et al, 2012;Pelkonen et al, 2012). Nevertheless, studies using omics and systems biology approaches should be particularly good at generating new hypotheses on mechanisms for the effects of TCM and these hypotheses would need many additional approaches to substantiate them.…”
Section: Discussionmentioning
confidence: 89%
“…This confidence was reflected by the opinions of GP-TCM members in the "Grand Issues" survey and supported by the recent research developments reviewed in this special issue Jia et al, 2012;Pelkonen et al, 2012). Nevertheless, studies using omics and systems biology approaches should be particularly good at generating new hypotheses on mechanisms for the effects of TCM and these hypotheses would need many additional approaches to substantiate them.…”
Section: Discussionmentioning
confidence: 89%
“…One such study on the anti-arthritic efficacy of latex proteins has been reported recently [15]. Numerous studies based on the quality assessment using chemometric analysis and omics approach have reported variation in the composition of constituents in the herbal medicines which have been attributed to seasonal changes, geographical conditions, or the processing of the plant material [18,33]. The qualitative and quantitative uniformity of the phytoconstituents present in plant-derived preparations are important from the point of their safety and efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…• Traditional (holistic) medicines are often mixtures, which do not fit well to the general set-up of clinical (reductionistic) trials [27,28].…”
Section: Clinical Evidence Of Safety and Efficacymentioning
confidence: 99%